1970
DOI: 10.4314/ejhs.v28i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Different Doses of Cyclophosphamide on Liver and Kidney Tissue in Swiss Albino Mice: A Histopathological Study

Abstract: BACKGROUND: Cyclophosphamide (CPA) is an anti- cancer drug, used in chemotherapy. This is a toxic drug which targets the cancer cells and also the normal cells of the body. The original compound is inactive in vitro and exercises its biologic action through metabolites, chiefly phosphoramide mustard. The objective is to study the harmful effects of this drug on liver and kidney tissues.METHODS: To study the effect of cyclophosphamide on histology of liver and kidney, 40 adult male mice were taken and divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…While, the tubular changes were demonstrated as vacuolations of tubular epithelial cells, dark stained nuclei with exfoliation of other nuclei and loss of PAS reaction at the brush borders of PCTs. Similar results reported by other researchers and these changes suggested increase in the oxidative stress with reduction of antioxidant factors [37,38] . In CPA treated rats, the Mallory's trichrome sections of the renal cortex showed increasing of collagen fibers around the blood vessels and the renal tubules.…”
Section: Discussionsupporting
confidence: 92%
“…While, the tubular changes were demonstrated as vacuolations of tubular epithelial cells, dark stained nuclei with exfoliation of other nuclei and loss of PAS reaction at the brush borders of PCTs. Similar results reported by other researchers and these changes suggested increase in the oxidative stress with reduction of antioxidant factors [37,38] . In CPA treated rats, the Mallory's trichrome sections of the renal cortex showed increasing of collagen fibers around the blood vessels and the renal tubules.…”
Section: Discussionsupporting
confidence: 92%
“…Tissue inflammation is usually observed by histological observation of spleen and liver. So, any pathology in these tissues, reflected by lesions of immune organs may cause weakening of immune function ( Yu et al, 2018 , Bhat et al, 2018 ). In the present study, the histology revealed that CP caused destruction in spleen and liver tissues, which was significantly inhibited by combination doses.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of CP was supported by the former findings. 55 However, liver sections from the DADS group showed preserved normal architecture of the hepatic lobule with no expression of PCNA. In the same context, the preadministration of DADS to the CPtreated rats resulted in the amelioration of changes elicited by CP with slight vacuolization of hepatocytes, and weak positive expression of PCNA revealed the hepatoprotective concept of DADS.…”
Section: Discussionmentioning
confidence: 89%